Meningkatkan Kemampuan Pengenalan Huruf Melalui Media Papan Magnet Pada Anak Usia Dini - Mahda Yunita; Yusra; Russy Ranggayoni; Jufri (LSM Catimore dan Sahabat Jl. Paya Ilang/Pertamina Desa Lemah Burbana, Takengon, Aceh Tengah 24552, 2026)
Introducing letters to early childhood is an essential stage in developing early literacy skills and reading readiness. However, children often experience difficulties in distinguishing similar letter shapes, such as ‘b’ and ‘d’ or ‘m’ and ‘w’. This study aims to describe the improvement of letter recognition skills through the use of magnetic letter board media. The research employed a Classroom Action Research (CAR) design with data collection techniques including observation, interview, and documentation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results showed a significant improvement in children’s letter recognition ability after implementing the magnetic board media. In the first cycle, there were 3 children categorized as Very Well Developed (BSB), 4 children as Developing as Expected (BSH), 5 children as Beginning to Develop (MB), and 3 children as Not Yet Developed (BB). In the second cycle, the categories improved to 9 children (BSB), 3 children (BSH), 2 children (MB), and 1 child (BB). These findings indicate that the use of magnetic letter board media is effective in enhancing children’s letter recognition skills and in creating a more interactive and enjoyable learning environment.